Approaches to estimate body condition from slaughter records in reindeer - Olofsson, Anna; Danell, Öje; Forslund, Pär; Åhman, Birgitta (Rangifer, 2008)
Long-term fluctuations in population densities of reindeer and caribou are common, where pasture is the limiting resource. Pasture quality affects the nutritional status and production of the animals. Therefore, continuous information about changes in the grazing resources is important when making management decisions. The objective of this study was to investigate different possibilities of using routine and additional slaughter records as body condition indicators, and thereby indicators of pasture resources in the summer ranges of reindeer husbandry. Records from 696 reindeer slaughtered in the winter 2002/2003 were included in the study. We developed a model with carcass weight as body condition indicator and two different models combining fatness, conformation, carcass weight, and body size as body condition indicators. The results showed age and sex dependent differences between the variables, and differentiation of animal age and sex improved the precision of models. Adjusting weight for body size also improved weight as a body condition indicator in adults. Conformation and fatness had good resemblance to weight and body size adjusted weight and should preferably be included, together with carcass weight and body size measures, when estimating body condition from carcasses. Our analysis showed that using non-invasive slaughter records is a good and non-expensive method of estimating body condition in reindeer. Abstract in Swedish / Sammandrag:Tillvägagångssätt för skattning avkroppskondition hos ren från slaktregistreringarFluktuationer i ren- och caribou-populationers täthet över tiden är vanliga då betet är en begränsad resurs och beteskvalitén påverkar djurens kondition och produktion. Kontinuerligt uppdaterad information om förändringar i betesresurserna är viktigt i samband med beslutsfattande om förvaltning avresurserna. Syftet med denna studie var att utvärdera olika möjliga sätt att använda rutinregistreringar och extra registreringar vid slakt som konditionsindikatorer och därmed indikatorer för betestillstånd i sommarland inom rennäringen. Registreringar från 696 renar, slaktade under säsongen 2003/2003 användes i studien. Vi utvecklade en modell där slaktvikt var den enda indikatorn på kroppskondition, samt två modeller som kombinerade fett- och formklassificeringen med slaktvikt och kroppsstorlek som indikatorer på kroppskondition. Resultaten visade att renarnas ålder och kön ger skillnader i de olika variablerna och att modellernas noggrannhet ökar om djuren grupperas med tanke på ålder och kön. Att korrigera slaktvikten för kroppsstorlek ökade precisionen för vikt som konditionsindikator för vuxna djur. Fett- och formklassificeringen överensstämde väl med storlekskorrigerad slaktvikt och skulle med fördel kunna inkluderas tillsammans med slaktvikt och storlek för skattning avkroppskondition från slaktkroppar. Våra analyser visar att användning avslaktregistreringar är en bra och billig metod för att skatta kroppskonditionen hos renhjorden.